Change in sense of food safety associated with social connectedness and information sources—A 10-year longitudinal survey before and after the Fukushima nuclear power plant accident. (May 2021) - Kuroda, Y.; Goto, A.; Terauchi, H.; Suzuki, S.
Abstract: Objectives: This study analyzes the change in the sense of food safety over time, from 2 years before to 8 years after the Fukushima accident in 2011, and its association with social connectedness using cohort data, taking into account regional differences in Fukushima Prefecture. Study design: Repeated cross-sectional data from Fukushima Prefectural Government from 2009 to 2018 were used. Methods: We randomly selected 1300 people every fiscal year (FY). The survey gathered data on age, gender, occupation, residential region, and the explanatory variables 'sense of social connectedness' and 'recovery-related information source' (information source). The prefecture was divided into three regions for the survey—Hamadori region, where the nuclear power plant is located, Nakadori region, where the air dose rate after the earthquake was high, and in Aizu, far from the nuclear power station but has suffered from harmful rumors. Results: Focusing on FY 2014, when the sense of safety first showed recovery, we performed a binominal logistic regression analysis with 'sense of safety' as the outcome and 'sense of social connectedness' and 'information source' as the explanatory variables. The sense of safety significantly decreased in all regions in 2011 relative to earlier years. The sense of food safety decreased markedly in Hamadori and Nakadori but started to improve 3 years after the earthquake and reached the pre-earthquake level in 2018. The effect sizes were larger in the Hamadori region and in Nakadori than in Aizu. In FY 2014, multivariate analysis found that a sense of food safety was significantly positively associated with a sense of social connectedness, whereas the use of information from newspapers and TV and word of mouth was negatively associated. Conclusion: Although the recovery of a sense of food safety may take some time, a focus on social connectedness during recovery and scrutiny of information sources may facilitate recovery. Health communication has an important role when the provider sends information intelligibly and the recipient can distinguish good news from bad and link it to self-determination. It is necessary to improve literacy.